1965
DOI: 10.1128/jb.90.5.1467-1480.1965
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Bacterial L Forms and Their Parent Bacteria

Abstract: Light and electron microscopic studies were done on normal cells and L forms of Proteus mirabilis, Staphylococcus aureus, and Corynebacterium sp. grown in liquid media. Under the prevailing growth conditions, the L forms studied were morphologically indistinguishable from one another. They appeared as approximately spherical elements occurring singly or more often connected with each other by thinner portions of cell material. In sections of large L forms, the following structures were seen: a peripheral, trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1966
1966
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Viability of these persisting forms was attested to by the sporadic reversions to classical S. faecalis bacteria that occurred in M-1infected cell systems after various latent periods. In addition, the large size range of particles (0.05 to 0.7 Am) occurring within vesicles of mature L-forms growing in pure culture is consistent with Weibull's speculation that smaller L-bodies inside or connected with larger L-forms may grow and divide (19). It might therefore be speculated that dense bodies can grow into immature, undifferentiated L-forms capable of reproduction only within a protected environment such as that found within the vesicle of the mature L-form, or perhaps within HEK cells.…”
Section: Discussionsupporting
confidence: 84%
“…Viability of these persisting forms was attested to by the sporadic reversions to classical S. faecalis bacteria that occurred in M-1infected cell systems after various latent periods. In addition, the large size range of particles (0.05 to 0.7 Am) occurring within vesicles of mature L-forms growing in pure culture is consistent with Weibull's speculation that smaller L-bodies inside or connected with larger L-forms may grow and divide (19). It might therefore be speculated that dense bodies can grow into immature, undifferentiated L-forms capable of reproduction only within a protected environment such as that found within the vesicle of the mature L-form, or perhaps within HEK cells.…”
Section: Discussionsupporting
confidence: 84%
“…Small, spherical, densely packed cells without apparent nuclear material, which have been previously defined as elementary corpuscles (2), were observed, but morphological evidence of their derivation from the larger forms could not be appreciated. Small cells within large cells, as previously described (1,10,15) in broth cultures of L-phase variants, likewise were not observed.…”
supporting
confidence: 79%
“…3) had the appearance of triple-layered "unit membranes" (31). Walls of gram-negative bacteria have often been characterized as "unit membranes," but recent electron microscopic studies have revealed a more complex structure of such walls when they are sectioned in situ (7,12,21,40). The present study thus shows that subcellular structures may have different appearances in the intact cell and after isolation.…”
Section: Discussionmentioning
confidence: 61%